The Influence of Motivation and Tourist Loyalty on Interest in Visiting Agro-tourism - Nur Chrisa Ferdiyanti; Juliani Dyah Trisnawati; Siti Rahayu (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Agrotourism is a form of tourism that involves visitors in activities related to agriculture, plantations, and other agro-based experiences. The increasing number of agrotourism destinations has created competition, making visitor loyalty essential for maintaining these attractions. Tourist loyalty can be influenced by high-quality experiences and overall satisfaction during visits to agrotourism sites. Additionally, tourists' motivation to visit agrotourism also affects their loyalty. This study was conducted to assess the relationship between loyalty to specific attractions and overall tourist destinations, as well as to examine the effect of motivation on visitor loyalty to agrotourism in Region K. The research employed a quantitative method using a five-point Likert scale for measurement. Data analysis was conducted using SmartPLS 4.0 software. A total of 314 responses were collected through a questionnaire distributed via Google Forms. The results of this study indicate that motivation influenced by pull factors does not affect satisfaction, whereas push factors do. Motivation has an impact on the quality of the experience. Furthermore, experience quality influences both satisfaction and loyalty. Satisfaction, in turn, affects loyalty. Lastly, attraction loyalty contributes to destination loyalty.